PENGEMBANGAN E-LKPD BERBANTUAN APLIKASI WIZER.ME MATERI TRANSFORMASI ENERGI DI SEKITAR KITA: PENGEMBANGAN E-LKPD BERBANTUAN APLIKASI WIZER.ME MATERI TRANSFORMASI ENERGI DI SEKITAR KITA - Muhamad Ramadan; Elly Sukmanasa; Jaja Sudarjat (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Muhamad Ramadan. 037121050. This research is a Research and Development (R&D), which is a series of systematic activities carried out to create new products, services, or processes or develop and improve existing products, services, or processes based on research findings. The ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). This research aims to develop E-LKPD with the help of a Wizer.me application about Energy Transformation Around Us. This research was conducted at Dewi Sartika 3 State Elementary School, Bogor City in the odd semester of the 2025/2026 academic year. In this study, validation tests were carried out on E-LKPD products by media, language, and material experts. The validation results by media experts obtained 85% with very feasible criteria, language experts obtained 98% with very feasible criteria, and by material experts 92% with very feasible criteria. The results of the student response questionnaire were 97% with a very good category. This demonstrates that the developed e-LKPD can be used by students in the learning process at school. The results indicate that the e-LKPD, supported by the Wizer.me application, is an effective and practical application for learning about energy transformation around us. This application can increase interaction, increase student enthusiasm and interest in learning, and facilitate teachers in creating online assignments, thus increasing student enthusiasm and active participation in learning. It can also facilitate teachers in conducting evaluations during learning.